Molecular diagnosis of leukemia. (June 2012) - Mason, Joanne; Griffiths, Michael
The diagnosis of leukemia relies upon a multiparametric approach involving a number of different pathology disciplines. Molecular methods are increasingly employed to help refine diagnosis, establish prognosis and determine the most appropriate treatment, including rational therapies targeting the underlying genetic lesion. This review aims to highlight some of the molecular techniques commonly used in the diagnosis of leukemia using relevant examples. The focus is on procedures in current use and technologies showing promise in the research setting that are likely to enter clinical use in the near future. The list is not exhaustive, and this article concentrates on diagnosis of leukemia; techniques used to monitor response to therapy and molecular residual disease are mentioned but have not been covered extensively.